Formação de intérpretes de Libras e Língua Portuguesa: encontros de sujeitos, discursos e saberes - Nascimento, Marcus Vinícius Batista (2016)
This dissertation aims to generally discuss the unpredictability, immediateness, discursivity and norms of interlanguage interpretation and its effects on the professional training of experienced or beginning Brazilian Sign Language and Portuguese Language Interpreters. We explore the enunciative-discursive complexity of this language activity as we consider the semiotic-ideological dimensions of the languages involved and the concreteness of its realization based on the needs of the interactants of the communicative situation and its striking dimension of its “language-as-work” condition. By means of a theoretical triangulation between Bakhtinian studies, ergology and interpreting studies, we transferred the self-confrontation methodology, originally developed by French linguist Daniel Faïta in the Activity Clinic context, to work activity intervention, to the context of professional training with a group of interpreters in a pós-graduação lato sensu [graduate continuing education program] in a course dedicated to the training interpretation in Libras-LP directionality of Brazilian Sign Language/Portuguese Translation and Interpretation offered by a private university in Sao Paulo. Students were divided into three pairs, and in each pair one student played the role of the Main Interpreter and the other, of the Supporting Interpreter. They also changed roles during the activity, in which they had to interpret texts from three different discourse genres, viz., Valedictorian speech, militant political discourse, prosaic opinionative discourse, at two moments: during the first class with no prior professional training action in sensu stricto and during the last class, after their professional training was over. In the last part of the course, the pairs watched the two video recordings and commented on the interpretations based on simple self-confrontation (when they talked about what they had done) and crossed self-confrontation (when the other peers talked about what they had done). The data show that the main interpreters of the interpretation activities, when placed before their own interpretation performance during self-confrontation, were able to learn, in the activity, much beyond what they know about their performance. In the first video, they recognized that their knowledge was a result of prior experience, and in the second that they discursively re-elaborated this knowledge according to their professional training. They also realized that the mobilized genres summoned for specific knowledge related to the interpretation activity: in the second video recording they used strategies they had learned during the professional training program, which were not used in the first one. This dialogical movement related to the interpretation activity before and after the professional training program prompted them to mobilize discourses on the I-for-myself, I-for-the-other, and other-for-me during self-confrontation, contributing, thus, to a shift in the perception of the I and the other classmates as workers who deal with an unpredictable, immediate, and striking activity. We hope that this research may contribute to the teaching/professional training of sign language interpretation, to studies on the relationship between language and work, and to discourse studies